2020
DOI: 10.1159/000509855
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Primary Care: A Review of Patient Follow-Up, Mortality, and Hospital Admissions following the Introduction of an AKI Alert System

Abstract: Background/Aims: In February 2017, our laboratory implemented an electronic AKI flagging system for primary care using the NHS England AKI detection algorithm. Our study investigated the impact on patient follow-up, hospital admission, length of stay, and mortality. Methods: Primary care results March 2017-February 2018 with an AKI test code were downloaded from the pathology computer. Results: Over 12 months, 1,784 AKI episodes were identified; 81.3% AKI1, 11.3%, AKI2, and 7.5% AKI3. A repeat creatinine was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Beyond the algorithm for AKI detection, a consistent nationwide alert system seems like a challenge in North America and the studies published from the UK have generally shown to be beneficial from a detection and alerting standpoint [ 43 , 65 , 73 , [79] , [80] , [81] ]. Some studies as discussed below have also reported improved clinical outcomes [ 65 , 80 , 81 ].…”
Section: Serum Creatinine (Scr) For Diagnosing Akimentioning
confidence: 99%
See 3 more Smart Citations
“…Beyond the algorithm for AKI detection, a consistent nationwide alert system seems like a challenge in North America and the studies published from the UK have generally shown to be beneficial from a detection and alerting standpoint [ 43 , 65 , 73 , [79] , [80] , [81] ]. Some studies as discussed below have also reported improved clinical outcomes [ 65 , 80 , 81 ].…”
Section: Serum Creatinine (Scr) For Diagnosing Akimentioning
confidence: 99%
“…AKI is also commonly encountered by non-specialized healthcare providers and given the lack of association with any specific symptoms; the syndrome of AKI enables evasion of early detection [ 81 ]. The popularized UK alert system based on modified KDIGO rules [ 71 ], has been extended to primary care in the UK, with the goal to manage community acquired AKI and evaluate impact on patient management and clinical outcome measures [ 80 , 81 ].…”
Section: Serum Creatinine (Scr) For Diagnosing Akimentioning
confidence: 99%
See 2 more Smart Citations
“…AKI can lead to serious complications, such as hydro-electrolytic disturbance, alterations in blood pressure control, impairment of acid–base homeostasis, rise of serum concentration of toxic metabolites and increased risk of drug overdose [ 19 , 20 ]. Moreover, AKI contributes to the production of diverse inflammatory mediators and vasoactive agents that play key roles in pathological mechanisms of several diseases [ 21 ].…”
Section: Introductionmentioning
confidence: 99%